Peritoneal mesothelioma causing small bowel obstruction in COVID-19 positive patient. Issue 10 (23rd October 2022) - Trivedi, Aakash; Hlayhel, Ahmad; Hooda, Zamaan; Foran, Lindsey; Wessner, Scott
Abstract: Mesothelioma is a disease process that can present in a variety of locations including the pleural, peritoneum and pericardium. Malignant peritoneal mesothelioma has been known to be a particularly aggressive type of tumor. We report a case of a patient who presented with a small bowel obstruction whose pathology revealed peritoneal malignant mesothelioma.